Profiles of Second Language Learners in Bilingual Education: A Comparative Study of the Characteristics of Finnish and American Students - Vuorinen, Petri (fi=Turun yliopisto|en=University of Turku|, 2009)
The purpose of this comparative study is to profile second language learners by exploring the factors which have an impact on their learning. The subjects come from two different countries: one group comes from Milwaukee, US, and the other from Turku, Finland. The subjects have attended bilingual classes from elementary school to senior high school in their respective countries. In the United States, the subjects (N = 57) started in one elementary school from where they moved on to two high schools in the district. The Finnish subjects (N = 39) attended the same school from elementary to high school. The longitudinal study was conducted during 1994-2004 and combines both qualitative and quantitative research methods. A Pilot Study carried out in 1990-1991 preceded the two subsequent studies that form the core material of this research. The theoretical part of the study focuses first on language policies in the United States and Finland: special emphasis is given to the history, development and current state of bilingual education, and the factors that have affected policy-making in the provision of language instruction. Current language learning theories and models form the theoretical foundation of the research, and underpin the empirical studies. Cognitively-labeled theories are at the forefront, but sociocultural theory and the ecological approach are also accounted for. The research methods consist of questionnaires, compositions and interviews. A combination of statistical methods as well as content analysis were used in the analysis. The attitude of the bilingual learners toward L1 and L2 was generally positive: the subjects enjoyed learning through two languages and were motivated to learn both. The knowledge of L1 and parental support, along with early literacy in L1, facilitated the learning of L2. This was particularly evident in the American subject group. The American subjects’ L2 learning was affected by the attitudes of the learners to the L1 culture and its speakers. Furthermore, the negative attitudes taken by L1 speakers toward L2 speakers and the lack of opportunities to engage in activities in the L1 culture affected the American subjects’ learning of L2, English. The research showed that many American L2 learners were isolated from the L1 culture and were even afraid to use English in everyday communication situations. In light of the research results, a politically neutral linguistic environment, which the Finnish subjects inhabited, was seen to be more favorable for learning. The Finnish subjects were learning L2, English, in a neutral zone where their own attitudes and motivation dictated their learning. The role of L2 as a means of international communication in Finland, as opposed to a means of exercising linguistic power, provided a neutral atmosphere for learning English. In both the American and Finnish groups, the learning of other languages was facilitated when the learner had a good foundation in their L1, and the learning of L1 and L2 were in balance. Learning was also fostered when the learners drew positive experiences from their surroundings and were provided with opportunities to engage in activities where L2 was used.

Tämä tutkimus on kvantitatiivis-kvalitatiivinen pitkittäistutkimus, jonka avulla pyritään luonnehtimaan toisen kielen oppijoiden profiileja ja oppimisen laatuun vaikuttavia tekijöitä kaksikielisessä opetuksessa. Tutkimuksen koehenkilöt tulevat kahdesta eri maasta: Yhdysvalloista ja Suomesta. Yhdysvalloissa koehenkilöt (N=57) opiskelivat Milwaukeen kaupungissa ensin ala-asteella, ja sitten kahdessa eri lukiossa. Suomen koehenkilöjoukko (N= 39) opiskeli koko koulu-uran samassa koulussa Turun kaupungissa. Pilottitutkimus toteutettiin vuonna 1990-1991, minkä jälkeen varsinainen tutkimusaineisto kerättiin vuosina 1994-2004. Tutkimuksen teoreettisessa taustassa luodaan aluksi katsaus Yhdysvaltojen ja Suomen kieli ja koulutuspolitiikkaan ja tarkastellaan erityisesti kaksikielisen opetuksen historiaa ja nykytilannetta sekä koulupoliittiseen päätöksentekoon vaikuttavia seikkoja. Kielen oppimisen teoreettisen taustan muodostavat vieraan kielen oppimisen mallit. Kognitiivispainotteisten mallien lisäksi lähtökohtia empiirisille tutkimuksille antavat sosiokulttuurinen teoria sekä ekologinen lähestymistapa kielen oppimiseen. Tutkimusmenetelminä käytettiin kyselylomakkeita, haastattelua ja oppimispäiväkirjoja. Aineistoa kuvataan tilastollisin menetelmin ja sisältöanalyysin periaatteita soveltaen. Tulosten mukaan kaksikieliset oppilaat suhtautuivat pääosin myönteisesti kahdella kielellä opiskeluun ja olivat motivoituneita kielten opiskeluun. Taustatekijöistä nousivat esille ensimmäisen kielen osaaminen ja vanhempien merkitys äidinkielen kehityksen tukemisessa. Tämä tulos korostui yhdysvaltalaisessa aineistossa. Yhdysvalloissa toisen kielen, englannin, oppimiseen vaikuttivat oppijan asenne valtakulttuurin edustajiin, koettu valtakielen puhujien negatiivinen suhtautuminen toisena kielenä englantia puhuviin ja osallistumismahdollisuudet ympäristön tarjoamiin aktiviteetteihin. Tutkimuksessa kävi ilmi myös yhdysvaltalaisten koehenkilöiden eristäytyminen englanninkielisestä valtakulttuurista ja suoranaiset pelot käyttää englantia kommunikoinnissa. Tutkimustulosten valossa näyttää siltä, että suomalainen, kielipoliittisesti yhdysvaltalaista neutraalimpi ympäristö oli suotuisa englannin oppimiselle. Ympäristön paineiden puuttuessa suomenkielisillä koehenkilöillä oli voitettavanaan vain omat asenteet ja motivoiduttava kielen opiskeluun. Englannin asema kansainvälisenä kommunikoinnin välineenä, ei niinkään valtakulttuurin kielenä, tarjosi suomalaisille koehenkilöille hyvän lähtökohdan oppimiselle. Sekä suomalaisilla että yhdysvaltalaisilla koehenkilöillä ensimmäisen kielen oppiminen ja sen tukeminen kotona edesauttoivat toisen kielen oppimista. Kahden kielen oppiminen onnistuu hyvin, kun niiden oppiminen on tasapainossa koulussa ja ympäristön asenne on positiivinen toisen kielen käyttäjiä kohtaan ja tarjoaa mahdollisuuksia toisen kielen käyttämiseksi.